Crystal structure and unique lamellar thickening for poly(l-lactide) induced by high pressure. (26th June 2019) - Huang, Shaoyong; Li, Hongfei; Jiang, Shichun
Abstract: Crystal structure and lamellar thickening of poly(l -lactide) (PLLA) prepared with and without high pressure were investigated via DSC and in situ synchrotron WAXS/SAXS. α and α′ and some β crystals were found in the PLLA specimens isothermally crystallized at 165 °C under pressure higher than 500 bar. Lamellar thickening via melt-recrystallization and crystal transformations of α′ -to- α and β -to- α crystals were observed upon heating. The SAXS peak first showed up at q ∼0.29 nm −1, corresponding to the long period ( L ) of ∼22 nm. When the annealing temperature was raised to ∼170 °C, an unusual scattering peak corresponding to long period ∼43 nm showed up. This latter scattering peak is absent in PLLA prepared at atmospheric pressure. The results suggest a precursor with more extended chain conformation is probably produced during the crystallization under high pressure and the melting processes, which facilitated fast thickening by the fusion of adjacent lamellae via chain-sliding into lamellae of doubled thickness. Graphical abstract: Crystal Structures of PLLA prepared under high pressure and the two lamellar thickening process upon heating. Image 1 Highlights: Crystal structures of PLLA under high pressures were thoroughly investigated via in situ WAXS/SAXS. Three crystal forms of PLLA as a function of pressure was observed. Doubling thickening for PLLA crystals via chain sliding and the structure evolution were studied.